The accuracy of burn depth diagnosis: Clinical assessment before and after enzymatic debridement. Issue 4 (October 2021) - Mataro, Ilaria; Giudice, Giuseppe; Elia, Rossella; D'Alessio, Roberto; Maggio, Giulio; Paolo Bianchi, Francesco; Di Franco, Livia; Razzano, Sergio; Vestita, Michelangelo
Highlights: Accurate assessment of burn depth is a critical goal in the management of burn patients. Nexobrid® increases the specificity and sensitivity of burn depth assessment. This results in less surgery, with improvement of patients' outcomes. Abstract: Introduction: The most common technique used to determine burn depth is clinical assessment by experienced burn surgeons, although this has been shown to be reliable in only 60–75% of the cases. Overestimation of burn depth may result in needles surgery, while burn depth underestimation can led to an increased length of stay in the hospital, risk of contracture and hypertrophic scar formation. The aim of this study was to assess the clinical evaluation of burn depth before and after enzymatic debridement with Nexobrid®. Methods: The study model was retrospective. 69 patient records were collected at our burn units, from Jan 2018 to Jan 2019. Each target wound was directly assessed by a single expert physician before and after enzymatic debridement. It was investigated whether the expert, by single wound, would have indicated the need for skin grafts before treatment with Nexobrid® and after treatment. Results: Prior to treatment with Nexobrid®, the expert physician assessed that a graft was necessary for 47/69 patients (68.1%). Following debridement, the same expert deemed that the patients needing a graft were 19/69 (27.5%); analysing K-agreement, a 40.6% discrepancy between the pre and post-treatment opinion with Nexobrid® was observed. Discussion: The use of Nexobrid® enzymatic debridement can positively affect burn depth clinical assessment, increasing its specificity and sensitivity, without any need for delay. This can lead to a significant change in clinical practice, minimizing the use of surgery, therefore increasing quality and precision of the reconstructive phase.